Composite zirconia ceramic microbead and preparation method thereof
By using the combination of yttrium-stabilized zirconia, alumina, magnesium oxide and modified silicon nitride, the problem of insufficient hardness and wear resistance of zirconia ceramic microbeads under high temperature conditions is solved, and higher hardness and wear resistance are achieved, and it is suitable for grinding of medium and high temperature conditions and high hardness materials.
Patent Information
- Application Number
- CN202510012026.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The existing zirconia ceramic microbeads have poor performance under high temperature conditions, low hardness and insufficient wear resistance, which limit their application in the fields of medium and high temperature conditions and high hardness material grinding.
The hardness and wear resistance of the microbeads are improved by the surface coating treatment of the modified silicon nitride by 75 to 85 parts by mass of yttrium stabilized zirconia, 15 to 25 parts by mass of alumina, 0.2 to 1 part by mass of silicon dioxide, 0.2 to 0.5 parts by mass of magnesium oxide, and 2 to 5 parts by mass of modified silicon nitride.
The hardness and wear resistance of composite zirconia ceramic microbeads are improved, self-wear is reduced, and a uniform and dense microstructure is formed, which enhances the stability and efficiency during the grinding process.
Smart Images

Figure CN119683996A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of zirconia ceramic microbeads, and in particular to composite zirconia ceramic microbeads and a preparation method thereof. Background Art
[0002] Ultrafine grinding equipment is widely used in new energy battery materials, paints, coatings and other fields. The materials are crushed through various complex movements such as mutual collision and extrusion of grinding media. In the use of ultrafine grinding equipment, the choice of grinding media is a very important issue, which determines the cost and efficiency of the crushing process and the quality of the crushed products. Common grinding media on the market include glass balls, steel balls, alumina balls, zirconia balls, etc. Among them, glass beads have low strength, high wear and easy to pollute materials; steel balls are less used due to their poor corrosion resistance and wear resistance; alumina balls (the main crystal phase is α-alumina) are mainly used for grinding hard mineral materials, but alumina materials have low fracture toughness and poor wear resistance, and are not suitable for high-speed sand mills; zirconia has a high specific gravity and good comprehensive performance, and is a high-end grinding material, but the price of zirconia and the reasons for phase change aging also limit its use in medium and high temperature conditions, and its hardness is lower than that of alumina balls, which limits its application in the field of grinding high hardness materials.
[0003] In order to improve the comprehensive performance of zirconium oxide, researchers have made some improvements accordingly. For example, CN112500834A discloses a composite zirconium oxide grinding ball for grinding high-purity zirconium carbide powder and a preparation method thereof. The composite zirconium oxide grinding ball is made by mixing yttrium-stabilized tetragonal zirconium oxide powder, monoclinic zirconium oxide powder, ultrafine alumina powder and graphite powder in a mass ratio of 60:10~30:1~20:1~5. When sintered in a reducing atmosphere, oxygen vacancies are controlled to reduce the impurity content, so that the hardness of the composite zirconium oxide grinding ball is improved, and the self-wear amount and impurity introduction during the grinding process are reduced. However, this method requires the formation of a reducing gas atmosphere, and the actual oxygen vacancies may be difficult to regulate with production fluctuations. CN116217270A discloses a production process for a diamond-coated dielectric ball on the surface of a zirconium oxide ball, wherein diamond micropowder is mixed with a composite binder to obtain a diamond-coated powder, and the diamond-coated powder is mixed with a wetting agent to wet the zirconium oxide ball, forming a zirconium oxide ball coated with a diamond film, thereby sintering to obtain a composite dielectric ball. However, this method does not test the wear and hardness of the composite dielectric ball, and the impact resistance of the diamond film coating may limit the application of the composite dielectric ball.
[0004] There is still a need to provide a zirconia ceramic microbead with high hardness and high wear resistance. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a composite zirconia ceramic microbead, which is prepared from 75-85 parts by mass of yttrium-stabilized tetragonal zirconia, 15-25 parts by mass of aluminum oxide, 0.2-1 parts by mass of silicon dioxide, 0.2-0.5 parts by mass of magnesium oxide, and 2-5 parts by mass of modified silicon nitride.
[0006] Zirconia has three crystal structures under normal pressure, namely cubic phase, tetragonal phase and monoclinic phase. Under normal pressure and temperature, the stable crystal of zirconium oxide is monoclinic phase, but when the temperature of monoclinic zirconium oxide rises to 1170℃, it will be transformed into tetragonal zirconium oxide, and the volume will shrink as the phase change process occurs. When the temperature of tetragonal zirconium oxide drops to 950℃, it will be transformed into monoclinic zirconium oxide, and this process will produce volume expansion. In order to prevent the cracking of zirconium oxide ceramics during sintering, it is necessary to stabilize zirconium oxide. Common stabilizers include yttrium oxide, cerium oxide, magnesium oxide, calcium oxide, etc., which can replace zirconium to form a substitution solid solution to prevent crystal transformation. Yttrium-stabilized tetragonal zirconium oxide has good high temperature resistance, chemical corrosion resistance, wear resistance, oxidation resistance, high hardness and other characteristics, and at the same time has a large thermal expansion coefficient, a small heat capacity and thermal conductivity, so the present invention uses it as a base material. Alumina has the characteristics of high hardness, high temperature stability and chemical stability, but its fracture toughness is low and its wear resistance is poor, so it is used as an auxiliary material.
[0007] Silicon nitride is a covalently bonded compound, and its basic structural unit is Tetrahedron, silicon atoms are located at the center of the tetrahedron, and nitrogen atoms are located at the four vertices of the tetrahedron, forming a continuous and strong network structure. Based on the unique structure, silicon nitride has high Mohs hardness and strength, and the strength decreases slowly with the increase of temperature. At the same time, it has good thermal conductivity and a small thermal expansion coefficient. If the addition of silicon nitride is well compatible with the formulation ingredients, it is beneficial to improve the hardness and wear resistance of the composite zirconia ceramic microbeads. However, it is difficult for nano silicon nitride to be evenly dispersed in the yttrium-stabilized tetragonal zirconia slurry system after direct addition, which makes the microstructure of the composite zirconia ceramic microbeads uneven, but increases the amount of self-wear and brings more impurities to the ground material. Therefore, it is necessary to modify the surface of nano silicon nitride to enhance its bonding performance with the formulation materials. Polyvinyl pyrrolidone has good film-forming properties, and its melting point varies according to the molecular weight, which is about 110~180°C. After dispersing nano-silicon nitride and polyvinyl pyrrolidone in alcohol, the temperature is lowered to allow polyvinyl pyrrolidone to crystallize and coat the nano-silicon nitride to form modified silicon nitride.
[0008] Furthermore, the preparation method of the modified silicon nitride comprises: Polyvinyl pyrrolidone, nano silicon nitride and alcohol are mixed in a mass ratio of 1-5:0.5-2:80-150, and stirred at a first temperature to obtain a suspension; The suspension is stirred at a second temperature to allow polyvinyl pyrrolidone to crystallize and form a coating on the surface of the nano silicon nitride, and insoluble matter is collected to obtain modified silicon nitride.
[0009] In order to improve the coating of polyvinyl pyrrolidone, heptadecafluorodecyltrimethoxysilane is added in the coating-crystallization process to reduce the surface tension of nano-silicon nitride and improve the dispersibility of nano-silicon nitride to form a more uniform coating.
[0010] Furthermore, after polyvinyl pyrrolidone, nano silicon nitride and alcohol are mixed, heptadecafluorodecyltrimethoxysilane is added in an amount of 0.1 to 0.5 times the mass of the nano silicon nitride.
[0011] Furthermore, the stirring at the first temperature is specifically stirring at 140-160° C. and a rotation speed of 300-500 rpm for 3-18 hours; The stirring at the second temperature is specifically stirring at 20-30° C. and a rotation speed of 50-100 rpm for 1-5 hours; The median particle size of the nano silicon nitride is 20-100 nm; The alcohol has a boiling point above 180°C.
[0012] In the present invention, there is no need to strictly limit the molecular weight of polyvinyl pyrrolidone and the type of alcohol. For example, the molar mass of polyvinyl pyrrolidone can be 10000-400000 mol / g; the alcohol can be at least one of n-nonanol, 2-nonanol, n-decanol, etc.
[0013] Furthermore, the median particle size of the yttrium-stabilized tetragonal zirconia is 0.2-0.6 μm; The median particle size of the aluminum oxide is 0.3-0.8 μm; The median particle size of the silicon dioxide is 0.5-1 μm; The median particle size of the magnesium oxide is 0.2-0.6 μm.
[0014] The present invention also provides a method for preparing the above-mentioned composite zirconia ceramic microbeads, comprising: Yttrium-stabilized tetragonal zirconia, aluminum oxide, silicon dioxide, magnesium oxide, modified silicon nitride and water are mixed and ground to obtain a slurry; The slurry is granulated by spraying to form spherical particle powder; The spherical green body is formed by mixing spherical particle powder with water and rolling them; The spherical green body is sintered to obtain composite zirconia ceramic microbeads.
[0015] In the present invention, after yttrium-stabilized tetragonal zirconia, alumina, silica, magnesium oxide, modified silicon nitride and water are mixed and ground, a certain proportion of a dispersant may be added during grinding. This is a conventional operation in the art. The type of the dispersant does not need to be strictly limited and may be sodium polyacrylate, ammonium polyacrylate, etc. The amount added may be 0.1% to 0.5% of the total mass of the slurry.
[0016] Furthermore, the median particle size of the slurry is less than 0.5 μm and the solid content is 40% to 60%.
[0017] Furthermore, the spray granulation is performed at a rotation speed of 9000-10000 rpm, an inlet temperature of 200-250°C, and an outlet temperature of 100-120°C.
[0018] Furthermore, the sintering is carried out at a temperature of 1400-1450° C. for 1-5 hours.
[0019] Furthermore, a polishing operation is also included after the sintering is completed.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses yttrium-stabilized tetragonal zirconia as the base material, supplemented with alumina and modified silicon nitride, and utilizes the high hardness of alumina and the good bonding of modified silicon nitride in the formula to improve the overall wear resistance. The results show that the addition of modified silicon nitride is conducive to the formation of a uniform and dense microstructure, which can reduce the probability of grain shedding, thereby reducing the grinding of microbeads. The composite zirconia ceramic microbeads prepared by the present invention have high hardness and low self-wear. At the same time, the raw material source is wide, the preparation method is simple, and it has a good market prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 A flow chart showing a method for preparing composite zirconia ceramic microbeads of the present invention is shown; Figure 2 A photograph of composite zirconia ceramic microbeads prepared by the present invention is shown; Figure 3 The scanning electron microscope image of the modified silicon nitride prepared in Example 1 is shown; Figure 4 The scanning electron microscope image of the modified silicon nitride prepared in Example 3 is shown; Figure 5The transmission electron microscope image of the modified silicon nitride prepared in Example 3 is shown; Figure 6 The scanning electron microscope image of the composite zirconia ceramic microbeads prepared in Comparative Example 2 is shown; Figure 7 The scanning electron microscope image of the composite zirconia ceramic microbeads prepared in Example 1 is shown; Figure 8 The scanning electron microscope image of the composite zirconia ceramic microbeads prepared in Example 3 is shown. DETAILED DESCRIPTION
[0023] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0024] Some of the raw materials used in the examples and comparative examples of the present invention are described as follows: Yttrium-stabilized tetragonal zirconia, with a median particle size of 0.5 μm and a mass fraction of zirconium oxide and zirconium oxide greater than 99.5%, customized by Zhejiang Jinkun Zirconium Industry Co., Ltd.; Alumina, with a median particle size of 0.7 μm and a content greater than 99.9%, was customized by Shandong Shoucheng Chemical Co., Ltd.; Silicon dioxide, with a median particle size of 0.6 μm and a content greater than 99.9%, was customized by Beijing Zhongke Keyou Technology Co., Ltd.; Magnesium oxide, with a median particle size of 0.6 μm and a content greater than 99.9%, was customized by Dashiqiao Meier Magnesium Products Co., Ltd. Nano silicon nitride, with a median particle size of 50 nm and a content greater than 99.9%, was purchased from Hebei Wenlun Metal Materials Co., Ltd.; Polyvinyl pyrrolidone, model PVP-K30, molecular weight about 40000 g / mol, purchased from Jinan Zhengkang Chemical Co., Ltd.; Heptadecafluorodecyltrimethoxysilane, model KH-1301, was purchased from Nantong Runfeng Petrochemical Co., Ltd.
[0025] Other raw materials not mentioned are common raw materials in the art. The above content is only to help illustrate the present invention and shall not be construed as a strict limitation of the present invention. Those skilled in the art can directly purchase the same / similar raw materials from the market or prepare them by themselves. These contents will not be repeated in the examples.
[0026] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1 like Figure 1 As shown, a method for preparing composite zirconia ceramic microbeads comprises the following steps: S1. Ingredients: weigh 80 kg yttrium-stabilized tetragonal zirconia, 20 kg alumina, 0.5 kg silicon dioxide, 0.3 kg magnesium oxide, 3 kg modified silicon nitride, 0.35 kg sodium polyacrylate, and 103.8 kg water; S2. Ball milling: adding yttrium-stabilized tetragonal zirconia, alumina, silicon dioxide, magnesium oxide, modified silicon nitride, sodium polyacrylate and water into a ball mill, and ball milling to obtain a slurry with a median particle size of 0.4 μm and a solid content of 50%; S3, spray granulation: the slurry is sent to the spray granulation dryer, the granulation tower atomizer speed is 9500rpm, the inlet temperature is 230℃, and the outlet temperature is 110℃ for granulation to obtain spherical granule powder with good fluidity and a diameter of 50μm; S4, ball forming: spray the spherical particle powder and glue into the ball forming machine, mix and roll to form a spherical green body with a diameter of 1 mm; S5, high temperature sintering: transfer the spherical green body to an automated kiln at 1430°C and keep it warm for 2 hours to obtain a rough material; S6. Surface polishing: Polish the surface of the rough material to reduce its surface roughness and obtain Figure 2 The composite zirconia ceramic microbeads shown.
[0028] Wherein, the preparation method of modified silicon nitride is: 2kg of polyvinyl pyrrolidone, 2kg of nano silicon nitride and 120kg of n-nonanol were mixed and stirred at 155°C and 350rpm for 12h; then the temperature was lowered to 25°C and the speed was reduced to 80rpm, maintained for 2h, and then the insoluble matter was collected by centrifugation and transferred to a constant temperature oven at 120°C for drying for 16h to obtain modified silicon nitride.
[0029] Example 2 A method for preparing composite zirconium oxide ceramic microbeads is basically the same as that of Example 1, except that: the method for preparing modified silicon nitride is: 2kg of polyvinyl pyrrolidone, 2kg of nano silicon nitride, 0.2kg of heptadecafluorodecyltrimethoxysilane and 120kg of n-nonanol were mixed, stirred at 155°C and 350rpm for 12h; then cooled to 25°C and reduced to 80rpm for 2h, then the insoluble matter was collected by centrifugation and transferred to a constant temperature oven at 120°C for drying for 16h to obtain modified silicon nitride.
[0030] Example 3 A method for preparing composite zirconium oxide ceramic microbeads is basically the same as that of Example 1, except that: the method for preparing modified silicon nitride is: 2kg of polyvinyl pyrrolidone, 2kg of nano silicon nitride, 0.8kg of heptadecafluorodecyltrimethoxysilane and 120kg of n-nonanol were mixed, stirred at 155°C and 350rpm for 12h; then cooled to 25°C and reduced to 80rpm for 2h, then the insoluble matter was collected by centrifugation and transferred to a constant temperature oven at 120°C for drying for 16h to obtain modified silicon nitride.
[0031] Example 4 A method for preparing composite zirconium oxide ceramic microbeads is basically the same as that of Example 1, except that: the method for preparing modified silicon nitride is: 2kg of polyvinyl pyrrolidone, 2kg of nano silicon nitride, 1kg of heptadecafluorodecyltrimethoxysilane and 120kg of n-nonanol were mixed, stirred at 155°C and 350rpm for 12h; then cooled to 25°C and reduced to 80rpm for 2h, then the insoluble matter was collected by centrifugation and transferred to a constant temperature oven at 120°C for drying for 16h to obtain modified silicon nitride.
[0032] Comparative Example 1 A method for preparing composite zirconium oxide ceramic microbeads is basically the same as that of Example 1, except that: the method for preparing modified silicon nitride is: 2kg of polyvinyl pyrrolidone, 2kg of nano silicon nitride, 1.2kg of heptadecafluorodecyltrimethoxysilane and 120kg of n-nonanol were mixed, stirred at 155°C and 350rpm for 12h; then cooled to 25°C and reduced to 80rpm for 2h, then the insoluble matter was collected by centrifugation and transferred to a constant temperature oven at 120°C for drying for 16h to obtain modified silicon nitride.
[0033] Comparative Example 2 A method for preparing composite zirconium oxide ceramic microbeads, comprising the following steps: S1. Ingredients: weigh 80 kg yttrium-stabilized tetragonal zirconia, 20 kg alumina, 0.5 kg silicon dioxide, 0.3 kg magnesium oxide, 3 kg nano silicon nitride, 0.35 kg sodium polyacrylate, and 103.8 kg water; S2. Ball milling: adding yttrium-stabilized tetragonal zirconia, alumina, silicon dioxide, magnesium oxide, nano-silicon nitride, sodium polyacrylate and water into a ball mill, and ball milling to obtain a slurry with a median particle size of 0.4 μm and a solid content of 50%; S3, spray granulation: the slurry is sent to the spray granulation dryer, the granulation tower atomizer speed is 9500rpm, the inlet temperature is 230℃, and the outlet temperature is 110℃ for granulation to obtain spherical granule powder with good fluidity and a diameter of 50μm; S4, ball forming: spray the spherical particle powder and glue into the ball forming machine, mix and roll to form a spherical green body with a diameter of 1 mm; S5, high temperature sintering: transfer the spherical green body to an automated kiln at 1430°C and keep it warm for 2 hours to obtain a rough material; S6. Surface polishing: polishing the surface of the coarse material to reduce its surface roughness, thereby obtaining composite zirconia ceramic microbeads.
[0034] Comparative Example 3 A method for preparing composite zirconium oxide ceramic microbeads, comprising the following steps: S1. Ingredients: weigh 80 kg yttrium-stabilized tetragonal zirconia, 20 kg alumina, 0.5 kg silicon dioxide, 0.3 kg magnesium oxide, 0.35 kg sodium polyacrylate, and 103.8 kg water; S2. Ball milling: adding yttrium-stabilized tetragonal zirconia, alumina, silica, magnesium oxide, sodium polyacrylate and water into a ball mill, and ball milling to obtain a slurry with a median particle size of 0.4 μm and a solid content of 50%; S3, spray granulation: the slurry is sent to the spray granulation dryer, the granulation tower atomizer speed is 9500rpm, the inlet temperature is 230℃, and the outlet temperature is 110℃ for granulation to obtain spherical granule powder with good fluidity and a diameter of 50μm; S4, ball forming: spray the spherical particle powder and glue into the ball forming machine, mix and roll to form a spherical green body with a diameter of 1 mm; S5, high temperature sintering: transfer the spherical green body to an automated kiln at 1430°C and keep it warm for 2 hours to obtain a rough material; S6. Surface polishing: polishing the surface of the coarse material to reduce its surface roughness, thereby obtaining composite zirconia ceramic microbeads.
[0035] Test Case The microstructures of the modified silicon nitride prepared in Example 1 and Example 3 were observed using a scanning electron microscope. The results are as follows: Figure 3 and Figure 4 As shown. Figure 3It can be seen that an uneven coating structure is formed on the surface of nano-silicon nitride, and there is a certain amount of agglomeration in nano-silicon nitride. Figure 4 It can be seen that the aggregation of nano-silicon nitride is reduced, but the coating is not obvious. The structure of the modified silicon nitride prepared in Example 3 was observed using a transmission electron microscope, as shown in FIG. Figure 5 As shown, it was further concluded that the addition of heptadecafluorodecyltrimethoxysilane improved the dispersion properties of nano-silicon nitride and the coating condition of polyvinyl pyrrolidone.
[0036] The microstructures of the composite zirconia ceramic microbeads of Comparative Example 2, Example 1 and Example 3 were also observed using a scanning electron microscope. The results were as follows: Figure 6~Figure 8 As shown. Figure 6 It can be seen that the microscopic surface of the microbeads prepared by adding nano-silicon nitride is uneven; Figure 7 It can be seen that the microbeads prepared by using polyvinyl pyrrolidone-coated silicon nitride are significantly more uniform than those in Comparative Example 2; Figure 8 It can be seen that the surface of the microbeads prepared with silicon nitride prepared using polyvinyl pyrrolidone and heptadecafluorodecyltrimethoxysilane has a uniform and dense microstructure.
[0037] The composite zirconia ceramic microbeads prepared in the examples and comparative examples were tested for density, hardness and self-wear in accordance with the standard JC / T 2136-2012 "Microcrystalline Zirconia Grinding Media Balls"; they were used for grinding high-purity zirconium carbide powder to detect the zirconium oxide content introduced by the belt mill, i.e., the wear amount; and the crushing strength of the composite zirconia ceramic microbeads prepared in the examples and comparative examples was tested using a crushing strength tester. These results are shown in Table 1.
[0038] Table 1 Test results of composite zirconia ceramic microspheres
[0039] It can be seen from the test results in Table 1 that the composite zirconia ceramic microbeads prepared in Examples 2 to 4 of the present invention have higher Vickers hardness, lower self-wear, lower wear loss and higher crushing strength. This is because the introduction of an appropriate amount of polyvinyl pyrrolidone and heptadecafluorodecyltrimethoxysilane to modify the nano-silicon nitride is beneficial to good coating of the nano-silicon nitride. The addition of modified silicon nitride is beneficial to the formation of a uniform and dense microstructure, which can reduce the probability of grain shedding, thereby reducing the grinding of the microbeads and improving the overall strength.
[0040] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite zirconia ceramic microbead, characterized in that: Prepared from 75-85 parts by mass of yttrium-stabilized tetragonal zirconia, 15-25 parts by mass of aluminum oxide, 0.2-1 parts by mass of silicon dioxide, 0.2-0.5 parts by mass of magnesium oxide, and 2-5 parts by mass of modified silicon nitride; The preparation method of the modified silicon nitride comprises: Polyvinyl pyrrolidone, nano silicon nitride and alcohol are mixed in a mass ratio of 1-5:0.5-2:80-150, and stirred at a first temperature to obtain a suspension; The suspension is stirred at a second temperature to allow polyvinyl pyrrolidone to crystallize and form a coating on the surface of the nano silicon nitride, and insoluble matter is collected to obtain modified silicon nitride.
2. The composite zirconia ceramic microbead according to claim 1, characterized in that: After polyvinyl pyrrolidone, nano silicon nitride and alcohol are mixed, heptadecafluorodecyltrimethoxysilane is added in an amount of 0.1 to 0.5 times the mass of the nano silicon nitride.
3. The composite zirconia ceramic microbead according to claim 1 or 2, characterized in that: The stirring at the first temperature is specifically stirring at 140-160° C. and a rotation speed of 300-500 rpm for 3-18 hours; The stirring at the second temperature is specifically stirring at 20-30° C. and a rotation speed of 50-100 rpm for 1-5 hours; The median particle size of the nano silicon nitride is 20-100 nm; The alcohol has a boiling point above 180°C.
4. The composite zirconia ceramic microbead according to claim 1, characterized in that: The median particle size of the yttrium-stabilized tetragonal zirconia is 0.2-0.6 μm; The median particle size of the aluminum oxide is 0.3-0.8 μm; The median particle size of the silicon dioxide is 0.5-1 μm; The median particle size of the magnesium oxide is 0.2-0.6 μm.
5. A method for preparing composite zirconia ceramic microbeads according to any one of claims 1 to 4, characterized in that: include, Yttrium-stabilized tetragonal zirconia, aluminum oxide, silicon dioxide, magnesium oxide, modified silicon nitride and water are mixed and ground to obtain a slurry; The slurry is granulated by spraying to form spherical particle powder; The spherical green body is formed by mixing spherical particle powder with water and rolling them; The spherical green body is sintered to obtain composite zirconia ceramic microbeads.
6. The method for preparing composite zirconia ceramic microbeads according to claim 5, characterized in that: The median particle size of the slurry is less than 0.5 μm and the solid content is 40% to 60%.
7. The method for preparing composite zirconia ceramic microbeads according to claim 5, characterized in that: The spray granulation was carried out at a rotation speed of 9000-10000 rpm, an inlet temperature of 200-250°C, and an outlet temperature of 100-120°C.
8. The method for preparing composite zirconia ceramic microbeads according to claim 5, characterized in that: The sintering is carried out at a temperature of 1400-1450° C. for 1-5 hours.
9. The method for preparing composite zirconia ceramic microbeads according to claim 5, characterized in that: Polishing is also included after sintering is completed.
Citation Information
Patent Citations
Composite zirconium oxide grinding ball for grinding high-purity zirconium carbide powder and preparation method of composite zirconium oxide grinding ball
CN112500834A
Production process of zirconium oxide ball surface diamond film coating medium ball
CN116217270A
Method for improving photovoltaic silicon nitride powder suspension property
CN105502314A
Zirconium oxide silicon nitride composite ceramic with high purity and high strength and preparation method thereof
CN106938932A
Modified nano SiO2 for building aluminum alloy template coating, fluorine-silicon modified coating as well as preparation method and application of fluorine-silicon modified coating
CN113980354A
Cited By
Zirconium oxide composite ceramic microbead and preparation method thereof
CN120136545A